Effect of a nonspiking neuron on motor patterns of the leech - Rodriguez, Mariano Julian (2012)
Premotor and motoneurons could play regulatory roles in motor control. We have investigated the role of a premotor nonspiking (NS) neuron of the leech nervous system in two locomotive patterns: swimming and crawling. The NS neuron is coupled through rectifying electrical junctions to all the excitatory motoneurons examined. In addition, activation of motoneurons evokes chemically mediated inhibitory responses in NS. During swimming and crawling, the NS membrane potential (VmNS) oscillated phase locked to the motor output. Hyperpolarization or depolarization of NS had no effect on swimming, but hyperpolarization of NS slowed down the crawling activity and decreased the motoneuron firing frequency. Depolarization of NS increased the motoneuron activity, and, at stages where the crawling pattern was fading, depolarization of NS reinstated it. Future work should determine if NS is actually a member of the central pattern generator or a regulatory element.